Designing a LKPD DigiLitNum Smartbook for Augmented Reality-Based Literacy and Numeracy Learning for Third Grade Elementary School Students - Debio Pararta Wiguna (Judikatif: Jurnal Desain Komunikasi Kreatif, 2025)
Augmented Reality (AR) books can be used as a first step in improving literacy and numeracy skills, especially in elementary schools. This is because Augmented Reality can facilitate students in improving their interactive learning skills wherever and whenever they want. This design aims to create a DigiLitNum or Digital Literacy and Numeracy Smartbook, which is a learning book with interesting content on Indonesian Language, Natural Sciences, and Mathematics that is easy for students to understand. In addition, this book has also been developed with the addition of a web-based application that utilizes Augmented Reality technology, which combines 3D animated objects. This design applies the Design Thinking method in an effort to obtain appropriate solutions to problems in designing the work. The design of this learning book aims to be the right choice of media for interactive and innovative learning.